Contrastive Study of Chinese and Indonesian Passive Sentences - Karina Fefi Laksana Sakti; Sunarti Sunarti; Aiga Ventivani (Makassar State University, 2020)
The purpose of this study was to compare Chinese and Indonesian passive sentences. This article belongs to the description of qualitative research. The research methods used in this paper are description and contrastive analysis method. The data source of this research is the Chinese and Indonesian references. The data of this research are in the form of descriptions of Mandarin passive sentences and Indonesian passive sentences. Data collection techniques in this research is to collect data relevant to research from various sources then arranged, analyzed, and drawn conclusions. First of all, describe the syntactic structures of Chinese and ndonesian passive sentences. Then comparing the syntactic structures of Chinese and ndonesian passive sentences to find out the difference of syntactic structures between Chinese and Indonesian passive sentences. The same point between Chinese and Indonesian passive syntactic structures is that both languages can change from active sentences to passive sentences, and sometimes there is no promoter. The difference between Chinese and Indonesian passive sentences lies in the position of the promoter; the morphology of predicate verb of Chinese passive sentences and Chinese active sentences are same, while the morphology of predicate verb of Indonesian Passive Sentences active sentences is different; and passive sentences in Indonesian can carry single verb. The predicate verb of the passive sentence in Chinese cannot be a single verb.